Micronutrient Supplementation Therapy in Subfertile Men: A Systematic Study - Akbar, Aidil (Buletin Farmatera, 2021)
In Indonesia, the infertility rate reaches 16% of couples of childbearing age, and 50% of cases are caused by male reproductive disorders. In the current study, micronutrient substitution therapy can increase sperm count and motility in subfertile men but has not shown consistent results. This study is a systematic study that aims to determine the effectiveness of micronutrient supplementation therapy for subfertile cases and what micronutrients are used for subfertile therapy. A literature search was carried out using the Google Scholar application with the keywords supplementation therapy in subfertile, from the results of a literature search using the prism method, 18 articles were found that included in the inclusion criteria, and it was found that almost all articles stated that micronutrition supplementation therapy in subfertile patients showed improved results. the number and motility of sperm cells and the micronutrients that are widely used are zinc, carnitine, Co-Q10, Vitamin E, Vitamin C, Selenium, Vitamin B12. It can be concluded that micronutrient supplementation can improve the number of live sperm cells and sperm motility.